2015
DOI: 10.3390/ma8074061
|View full text |Cite
|
Sign up to set email alerts
|

Endurance of Damping Properties of Foam-Filled Tubes

Abstract: The favorable energy-absorption properties of metal foams have been frequently proposed for damping or anti-crash applications. The aim of this paper is to investigate the endurance of these properties for composite structures, made by a metal or a hybrid metal-polymeric foam used as the core filling of a tubular metal case. The results of experimental tests are shown, run with two types of structures: 1) square steel tubes filled with aluminum or with hybrid aluminum-polymer foams; 2) round titanium tubes fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Often, the structure can be made even lighter, as the addition of foam can allow the reduction of the wall thickness without sacrificing performance [35]. Foam-filled components are also more vibration-resistant and therefore often have longer fatigue lives due to improved energy absorbency by the foam [36]. Several studies [37][38][39][40][41][42][43] have explored the production and use of polymer and metal foams for structural applications.…”
Section: Thin Cylinder Reinforcementmentioning
confidence: 99%
“…Often, the structure can be made even lighter, as the addition of foam can allow the reduction of the wall thickness without sacrificing performance [35]. Foam-filled components are also more vibration-resistant and therefore often have longer fatigue lives due to improved energy absorbency by the foam [36]. Several studies [37][38][39][40][41][42][43] have explored the production and use of polymer and metal foams for structural applications.…”
Section: Thin Cylinder Reinforcementmentioning
confidence: 99%
“…In recent years, many investigations have been focused on metallic foam fillers to improve the energy absorption and mechanical properties of thin-walled tubes. Moreover, studies have shown that metallic foams can increase the components' damping level [4], in some cases up to five times compared to the tube itself [5]. This has resulted in a focused attention towards application of FFTs as safety components such as antiintrusion bars [6], crash boxes [7], frame of coach structures [8], or bumpers [9] in the car industry.…”
Section: Introductionmentioning
confidence: 98%
“…the size of the cut section. Recently, in situ direct foaming has attracted attentions [4,11,15,25,29,38]. In this process, foaming of precursors which are combinations of metallic powder and gas releasing agent takes place directly inside the tube.…”
Section: Introductionmentioning
confidence: 99%
“…Use of metal foams as one of several components in multi-material, hybrid, and similar structures integral foams integral foam casting [ 53 , 54 , 55 ] integration of foam parts in metal castings two component processes for syntactic foams produced via metal injection molding (MIM) [ 56 ] sandwich structures Aluminium Foam Sandwich (AFS) [ 10 , 57 ] steel face sheet sandwich materials via foaming between face sheets [ 58 ] APM-based sandwich [ 59 ] CFRP-metal foam sandwich structures etc. foam-filled hollow components in situ foaming to achieve foam-filled tubes and extrusions [ 60 , 61 , 62 , 63 ] co-extrusion of conventional and foamable material followed by in situ foaming [ 8 ] ex situ foaming and subsequent adhesive bonding of cores to hollow metallic structures [ 61 , 64 , 65 ] ex situ foaming and subsequent adhesive bonding of cores to hollow CFRP structures, including use of metal foam parts as permanent core/mandrel in FRP production, e.g., filament winding [ 66 , 67 ] etc. hybrid foams Polymer foam-APM hybrids [ 68 , 69 ] etc.…”
Section: Introductionmentioning
confidence: 99%
“…foam-filled hollow components in situ foaming to achieve foam-filled tubes and extrusions [ 60 , 61 , 62 , 63 ] co-extrusion of conventional and foamable material followed by in situ foaming [ 8 ] ex situ foaming and subsequent adhesive bonding of cores to hollow metallic structures [ 61 , 64 , 65 ] ex situ foaming and subsequent adhesive bonding of cores to hollow CFRP structures, including use of metal foam parts as permanent core/mandrel in FRP production, e.g., filament winding [ 66 , 67 ] etc. …”
Section: Introductionmentioning
confidence: 99%